Outcomes after rib fractures: more complex than a single number - Kristin P. Colling; Tyler Goettl; Melissa L. Harry (Journal of Trauma and Injury)
Purpose Rib fractures are common injuries that can lead to morbidity and mortality. Methods Data on all patients with rib fractures admitted to a single trauma center between January 1, 2008 and December 31, 2018 were reviewed. Results A total of 1,671 admissions for rib fracture were examined. Patients’ median age was 57 years, the median Injury Severity Score (ISS) was 14, and the median number of fractured ribs was three. The in-hospital mortality rate was 4%. Age, the number of rib fractures, and Charlson Comorbidity Index scores were poor predictors of mortality, while the ISS was a slightly better predictor, with area under the receiver operating characteristic curve values of 0.60, 0.55, 0.58, and 0.74, respectively. Multivariate regression showed that age, ISS, and Charlson Comorbidity Index score, but not the number of rib fractures, were associated with significantly elevated adjusted odds ratios for mortality (1.03, 1.14, and 1.28, respectively). Conclusions Age, ISS, and comorbidities were independently associated with the risk of mortality; however, they were not accurate predictors of death. The factors associated with rib fracture mortality are complex and cannot be explained by a single variable. Interventions to improve outcomes must be multifaceted.